The impact of Mood on Sports Flow State in football players: a chain mediating model of Psychological Resilience and Achievement Motivation in Competition - Li, Jiang; Pan, Xiaofei (Frontiers in Psychology, 2025)
ObjectivesTo explore the relationship between Mood and Sport Flow State in football players, and to clarify the mediating roles of Psychological Resilience and Achievement Motivation in Competition.MethodsConvenience sampling was used to conduct a questionnaire survey on 388 football players. Use Profile of Mood State (POMS), Smooth Experience Scale-2 (SES-2), Connor Davidson Resilience Scale (CD-RISC), and Achievement Motivation Scale (AMS) to evaluate the Mood, Sport Flow State, Psychological Resilience, and Achievement Motivation in Competition of football players. Pearson correlation analysis and mediation analysis were used to investigate the relationship between the four variables of Mood, Sport Flow State, Psychological Resilience, and Achievement Motivation in Competition among football players.ResultsFootball players’ mood has a negative impact on Sport Flow State, Psychological Resilience, and Achievement Motivation In Competition, while Sport Flow State, Psychological Resilience, and Achievement Motivation In Competition have a mutually positive impact. Psychological Resilience has a positive impact on Achievement Motivation in Competition. The mediating effect of Psychological Resilience (POMS → CD-RISC → SES-2) accounts for 26.9% of the total effect (r = −0.014, 95% CI −0.020∼−0.009), Achievement Motivation in Competition (POMS → AMS → SES-2) accounts for 17.3% of the total effect (r = 0.009,95% CI −0.013∼−0.005), and the chain mediating effect of Psychological Resilience and Achievement Motivation in Competition (POMS → CD-RISC → AMS → SES-2) accounts for 32.6% of the total effect (r = −0.017, 95% CI −0.022∼−0.013).ConclusionFootball player Mood has a significant negative impact on Sport Flow State, but its actual predictive ability for Sport Flow State is very small. Psychological Resilience and Achievement Motivation in Competition play a chain mediating role in this relationship.